# Question:decompose the equation

## Question:decompose the equation

Maple
`How to achieve that Maple, decompose the equation:   `
```Diff(x,t,t)+3*Diff(x,t)^2+5*x=1;                        / 2  \            2                                  |d   |     / d   \                                   |-- x| + 3 |--- x|  + 5 x = 1                        \    /     \ dt  /           -3*Diff(x,t)^2-5*x+1 = Diff(x,t,t);                                  2              2                             / d   \              d                           -3 |--- x|  - 5 x + 1 = -- x                           \ dt  /                  in this two:Diff(x[2],t)=-3*x[2]^2-5*x[1]+1;                       d                2                                   --- x[2] = -3 x[2]  - 5 x[1] + 1                       dt                             Diff(x[1],t)=x[2];                                d                                            --- x[1] = x[2]                                dt            Es posible? alguna sugerencia?
HerClau```
﻿